Peningkatan Kinerja UMKM Melalui Peran Strategi Pemasaran di Desa Lilibooi, Leihitu Barat, Kabupaten Maluku Tengah - Pelupessy, Merry Margareth; Tehuayo, Erlinda; Tubalawony, Jacsy; Tabelessy, Walter (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
Lilibooi Village is in West Leihitu District, Central Maluku Province. Lilibooi Village has great natural potential so that apart from attracting tourists to visit because of its natural beauty, it is also because of its large natural resources in the agricultural sector. Small and Medium Enterprises (SMEs) in this village are already running but are still on a small scale and need to be improved. There are many challenges faced by SMEs today, including SMEs in Central Maluku, especially in Lilibooi, which are still faced with a lack of understanding about the importance of information technology, online promotions, business locations and product quality. Marketing strategies are needed to increase the sales volume of each SME player and introduce SME products more widely. The aim of this community service activity is to answer the problems faced by SMEs in Lilibooi Village by providing outreach and sharing knowledge so that SME actors in the village can apply it to improve SME performance. The socialization material provided is related to several issues that are not yet understood so that it can encourage SME marketing. The result of this service is the absorption of knowledge and skills from SME players in understanding the role of marketing strategy through material in the form of applying technology to SME operations, promotions, business locations and product quality. The development of SMEs can have an influence on improving their performance. With this marketing strategy effort, it can increase the income of SME players.Keywords: Product Quality, Business Location, Promotion, Information Technology, SME